Three Sources of Inefficiency in Russian Science and Three Pillars for Innovation - A. A. Nikonova (Ekonomika Nauki)
The study aims to identify the reasons for the inefficiency of research and development (R&D) in Russia. It is guided by the principles of system economic theory, developed at the Central Economics and Mathematics Institute of the Russian Academy of Sciences. The study presents empirical data to demonstrate the significant impact of three main sources of R&D inefficiency: 1. The diverse structure of the Russian economy, which divides the science sector according to various characteristics, leads to low internal demand for domestic research and innovation. 2. The poor institutional quality of governance and dysfunctional governance systems, including regulatory instruments, income distribution, and criteria for evaluating scientific output, result in structural economic, scientific, and educational policies that are ineffective, leading to decreased motivation and reduced potential for science.3. The negative impact of the science sector, researchers, and the educational community on the socio-economic system is due to their depletion during periods of reform and their economic and institutional dependence on authorities, state policies, and recognition of researcher labor value. These three factors are closely related and contribute to the continued reproduction of problems, both in the creation of knowledge and its transfer to the economy. There is an ambiguity in the understanding of the term “efficiency of science” and the methods used to measure it, which prevents comparative analysis and decision-making to motivate actors. When discussing the fundamental factors of innovation activity efficiency, three pillars are identified: demand, the potential of science, and human potential, as well as qualified public administration. The direct and indirect connections between innovation activities and their impact on efficiency are discussed. A flexible approach to combining three different types of innovation models is recommended – linear, project-based, and ecosystem – as all three models rely on the same principles for achieving the best results in R&D and innovation.